(untitled) (Journal of the College of Basic Education, 2022)
The experiment was carried out using plastic pots in the uncovered plastic house of the Department of Science _ College of Basic Education / Al-Mustansiriya University for the growing season 2014-2015 to study the effect of potassium and gibberellic acid on some characteristics and yield components of the black seed plant (Nigella sativa L). The experiment was conducted according to a completely randomized design. Completely Randomized Design (CRD) as a factorial experiment with three replications for each treatment, and the Least Significant Difference (L.S.D.) test at the probability level of 0.05 was used to compare the mean of the treatments.